2022
DOI: 10.3390/antibiotics11101412
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Biofilm Inhibiting Activity of Advanced Glycation Endproduct Crosslink Breaking and Glycation Inhibiting Compounds

Abstract: Staphylococcus aureus is a Gram-positive bacterium that plays a role in the pathogenesis of skin lesions in diabetes mellitus, atopic dermatitis, and psoriasis, all of which are associated with elevated non-enzymatic glycation biomarkers. The production of biofilm protects resident bacteria from host immune defenses and antibiotic interventions, prolonging pathogen survival, and risking recurrence after treatment. Glycated proteins formed from keratin and glucose induce biofilm formation in S. aureus, promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(56 reference statements)
0
4
0
1
Order By: Relevance
“…Ascorbic acid, commonly known as vitamin C, is an essential dietary nutrient that is necessary for a variety of physiological processes in human body, including wound repair and collagen production [ 27 ]. Most animals are able to synthesize their own vitamin C. However, apes (including humans), monkeys (but not all primates), and some rodents must acquire it from dietary sources [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ascorbic acid, commonly known as vitamin C, is an essential dietary nutrient that is necessary for a variety of physiological processes in human body, including wound repair and collagen production [ 27 ]. Most animals are able to synthesize their own vitamin C. However, apes (including humans), monkeys (but not all primates), and some rodents must acquire it from dietary sources [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous phytochemicals, including carotenoids, have been reported to demonstrate antibiofilm and antimicrobial properties ( Kim et al., 2024 ). Astaxanthin, an algae-derived carotenoid has been reported to dwindle the biofilm growth in S. aureus by mitigating its adherence to the surface and in S. epidermidis by expressing a bactericidal effect ( Weintraub et al., 2017 ; Haasbroek et al., 2022 ). Additionally, a research investigation explores the antibiofilm characteristic of zeaxanthin, which disrupts the quorum sensing (QS) systems and inhibits biofilm formation in P. aeruginosa ( Gökalsın et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bacteria are able to manipulate the host immune response through the secretion of membrane vesicles, that play an essential role in the delivery of bacterial effectors promoting virulence, biofilm formation, signal transduction, cytotoxicity, resistance to antimicrobial skin fatty acids and in skin inflammatory disorders ( Gurung et al., 2011 ; Alpdundar Bulut et al., 2020 ; Kengmo Tchoupa and Peschel, 2020 ; Staudenmaier et al., 2022 ). Several studies have demonstrated the importance of staphylococcal biofilms in the pathogenesis of AD ( Allen et al., 2014 ; Sonesson et al., 2017 ; Di Domenico et al., 2018 ; Haasbroek et al., 2022 ). Most of our AD strains were strong biofilm producers, confirming the importance of biofilm in i) the increased resistance to the host immune responses, in ii) the reduced susceptibility to antimicrobials and in iii) inflammation, thus, promoting skin colonization and persistence.…”
Section: Discussionmentioning
confidence: 99%